A Feasibility study on Gum Candies Made of Carrageenan - Padre, Ida Felissa M. (Diliman, Quezon City College of Engineering, 2003)
Goodigles, flavored Chewing Gum, is a product made of a well abundant raw material in the Philippines- Carrageenan. The company that manufactures Goodiggles Chewing Gum shall be located at the Carmelray Industrial Park in Canlubang, Laguna. The company is a Filipino stock corporation, having the size of 23 workforce, and producing 163 million pieces of chewing gum candies per year. It employs a fully imported and automated chewing gum production line working on an 8-hour shift per day. Its suppliers are certified and are located in the Philippines. The company's main market is the end-user as well as retailers and aims to initially market its products to the three most populous regions (National Capital Region, Southern Tagalog Region and Central Luzon) in the country with a sound marketing strategy. The total project cost for making the product amounts to 37 Million with the bulk of its amount financed through loans. Equity financing is through shares amounting to 100,000. It is forecasted to earn at a rate of at least 42% a year. The company's project has also passed the financial tests, such as Break-Even-Analysis, Discounted Cash Flow Method, and Internal Rate of Return, making this carrageenan business a profitable venture.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 153 : Project Development and Management.
Keywords: Chewing gum industry; Carrageenan; Participatory monitoring and evaluation (Project management)